Obesity in junk food generation in Asia: A health time bomb that needs early defusing! - Rahman, Sayeeda (South East Asia Journal of Public Health, 2014)
South East Asia Journal of Public Health 2013; 3(1): 1-2 DOI: http://dx.doi.org/10.3329/seajph.v3i1.17703